2005
DOI: 10.1080/09602010443000137
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the left and right hemispheres to early recovery from aphasia: A SPECT prospective study

Abstract: This prospective study examined the relationship between post-stroke recovery of aphasia and changes in cerebral blood flow (CBF). To address the question of right hemisphere (RH) involvement in restitution of language, we tested the hypothesis that the increase in perfusion of the RH is crucial for early recovery from aphasia. Twenty-four right-handed patients with acute aphasia following left hemisphere (LH) ischaemic stroke were examined twice with a six-month interval. At each session CBF and language scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our patient had WM lesions in the corona radiata, pons and basal ganglia, as well as the internal capsule. The characteristics of speech such as imprecise articulation, mildly slower speech rate and repetition of first syllables [2,29] can be due to these lesions, but may also be the consequence of the right cerebellar vermis lesion shown on MRI. Anatomo-clinical studies Kent, 2001 [27] comparing speech and other motor dysfunctions in patients with cerebellar disease and dysarthria, showed that the midline structures of vermis and fastigial nucleus were the primary centers of the coordination of motor speech.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our patient had WM lesions in the corona radiata, pons and basal ganglia, as well as the internal capsule. The characteristics of speech such as imprecise articulation, mildly slower speech rate and repetition of first syllables [2,29] can be due to these lesions, but may also be the consequence of the right cerebellar vermis lesion shown on MRI. Anatomo-clinical studies Kent, 2001 [27] comparing speech and other motor dysfunctions in patients with cerebellar disease and dysarthria, showed that the midline structures of vermis and fastigial nucleus were the primary centers of the coordination of motor speech.…”
Section: Discussionmentioning
confidence: 97%
“…Speech and language disturbances secondary to vascular lesions in subcortical white matter (WM) and basal ganglia are heterogeneous and can influence several aspects of voice, speech and language [1,2,4,6]. These disorders are challenging because of a variety of cerebral structures and neurological circuits are involved [1].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative technique, called performance-correlation analysis using the principle that the intensity of brain activations is highly correlated with the frequency with which the neural elements are used during the imaging epoch was introduced for imaging (Silbersweig et al, 1995). It was further developed for speech motor studies (Braun et al, 1997; Fox et al, 2000; Ingham et al, 2004; Raboyeau et al, 2004; Jodzio et al, 2005; Rektorova et al, 2007), but thus far has not been applied to examine treatment outcomes. We therefore sought to apply performance correlation analyses to further investigate the brain correlates and the mechanisms of action characterizing successful LSVT LOUD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As Pizzamiglio, Galati, and Committeri (2001) note in their review, many studies to date have focused on the neural processing characteristics associated with recovery from aphasia (i.e., in the absence of treatment). Evidence of both homologousright hemisphere (RH) adaptationand increased left hemisphere (LH) perilesional activity has been found (e.g., Calvert et al, 2000;Cherney & Small, 2006;Fernandez et al, 2004;Heiss, Kessler, Thiel, Ghaemi, & Karbe, 1999;Jodzio, Drumm, Nyka, Lass, & Gasecki, 2005;Rosen, 2000;Saur et al, 2006;Szekeres, Ylvisaker,& Cohen, 1987). The respective roles of the right and left hemispheres continue to be debated with regards to the question of the effects of neuroplasticity in recovery from aphasia, however Crosson et al (2007) point out that the most fruitful approach to this question is not whether one or the other hemisphere plays a role in recovery, but rather, when and under what circumstances each hemisphere contributes to recovery.…”
Section: Introductionmentioning
confidence: 99%